2017
DOI: 10.3390/f8070222
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Biochemical Properties in a Cedar Plantation Invaded by Moso Bamboo

Abstract: Moso bamboo (Phyllostachys edulis) is one of the widely growing bamboo species in Asia. Because of its fast growth and aggressive rhizomes, it is reported to invade other forests and reduce the biodiversity of forest ecosystems. To determine the changes in soil nutrient conditions due to moso bamboo invasion, this research measured the difference in soil labile carbon (C) and nitrogen (N) contents in a Japanese cedar (Cryptomeria japonica) forest invaded by moso bamboo in central Taiwan. The content of soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…2015). In addition, recent studies have also reported that moso bamboo invasion affected physical, chemical, and biological soil properties (Lin et al 2014;Fukushima et al 2015;Shinohara and Otsuki 2015;Chang and Chiu 2015;Xu et al 2015;Wang et al 2016b;Song et al 2017;Li et al 2017a;Qin et al 2017;Shiau and Chiu 2017).…”
Section: Introductionmentioning
confidence: 99%
“…2015). In addition, recent studies have also reported that moso bamboo invasion affected physical, chemical, and biological soil properties (Lin et al 2014;Fukushima et al 2015;Shinohara and Otsuki 2015;Chang and Chiu 2015;Xu et al 2015;Wang et al 2016b;Song et al 2017;Li et al 2017a;Qin et al 2017;Shiau and Chiu 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Soil soluble N from compounds like NH 4 + KCl , NO 3 − KCl , and TDN KCl was higher in CONIF‐40 than either BROAD‐Nat sites, and this could be linked to the fact that young forests have more young leaves than do old forests. Soil organic C is not polar and therefore dissolves better in HW than under ion exchange (Shiau et al, 2017; Shiau & Chiu, 2017). Therefore, S b OC HW concentrations were higher than those of S b OC KCl at all three studied sites, and S b OC HW is typically considered to reflect the labile portion of soil C better than S b OC KCl (Shiau & Chiu, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that soil KCl‐ and hot water (HW)‐extractable C and N contents reflect the nutrients that can be readily metabolized by soil microorganisms, while acid‐hydrolyzable C is considered to be bioreactive C in soil (Xu et al, 1997). Extraction methods, such as KCl and HW, have been widely used to study various forest ecosystems and have proven that KCl‐ and HW‐extracted C and N contents are directly linked to microbial biomass (Huang et al, 2014; Shiau et al, 2017; Shiau & Chiu, 2017). In addition, acid‐hydrolyzable and recalcitrant C have been used to evaluate soil C quality under different types of plant cover (Wang, Chou, et al, 2016; Wang, Tian, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Soil total organic C (TOC) and total N (TN) were evaluated by the combustion method with an elemental analyzer (Fisons NA1500, ThermoQuest Italia, Milan, Italy). Soil labile C and N (soluble organic C: S b OC; soluble organic N: S b ON; ammonium: NH 4 + ; nitrate: NO 3 − ; total dissolved N: TDN) were extracted using a 2 M KCl extraction method [ 28 , 29 ]. Briefly, extracts were filtered from 5 g of soil and soaked with 50 mL KCl for an hour at 150 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…were extracted using a 2 M KCl extraction method [28,29]. Briefly, extracts were filtered from 5 g of soil and soaked with 50 mL KCl for an hour at 150 rpm.…”
Section: Aerobic Ch4 Oxidation Experiments and Dna-sip Gradient Fractimentioning
confidence: 99%